(25x...)-(...x8)=25x(4-8)=

less than a minute read Jun 11, 2024
(25x...)-(...x8)=25x(4-8)=

Solving the Equation: (25x...(4x8)) = (25x) (4-8)

In this article, we will solve the given equation step by step.

The Equation:

(25x...(4x8)) = (25x) (4-8)

Step 1: Evaluate the Expression inside the Parentheses

First, let's evaluate the expression inside the parentheses.

4x8 = 32

So, the equation becomes:

(25x...32) = (25x) (4-8)

Step 2: Evaluate the Expression (4-8)

Now, let's evaluate the expression (4-8).

4-8 = -4

So, the equation becomes:

(25x...32) = 25x(-4)

Step 3: Simplify the Equation

Now, let's simplify the equation.

(25x...32) = -100x

The Final Answer:

Thus, the final solution to the equation is:

(25x...(4x8)) = -100x

Featured Posts